Estimates of genetic distance, combining ability and heterosis for body weight of cross four populations of giant gourami, Osphronemus goramy Lacepede 1801 - Sularto Sularto; Rita Febrianti; Suharyanto Suharyanto (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2017)
The superior giant gourami can be obtained through hybridization. The purpose of this study was to estimate the genetic distance, combined ability, and crossbreeding heterosis at the age of eleven months from the four gourami populations: Kalimantan, Jambi, Majalengka, and Tasikmalaya. The study was conducted at the Research Institute for Fish Breeding Sukamandi. Genetic distance calculations were done by truss morphometric characterization with a sample of each of crossbred many as 30 individuals with the standard length range 3.5 - 12.2 cm. The data was analyzed using discrimi-nant analysis and continued with